1995
DOI: 10.1212/wnl.45.11.1980
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance on the Alzheimer's Disease Assessment Scale

Abstract: The cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-Cog) is used to monitor disease progression and treatment efficacy in clinical trials of Alzheimer's disease (AD). Using data from a 12-week drug trial, we retrospectively studied the effect of education on ADAS-Cog performance in a group of 444 patients with AD. The effect of education was statistically significant on baseline ADAS-Cog total scores. This effect remained statistically significant after controlling for age, gender, and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 0 publications
0
18
1
1
Order By: Relevance
“…Previous studies have generally found little or no influence of age, education, or gender on the ADAS-Cog score, although exceptions [2,15] to this general finding have also been reported. The present finding that performance on the Chinese ADAS-Cog was unrelated to education except at the low end (between 0 and 6 years) of the education spectrum is similar to the finding on the MMSE from a community study of 5,297 Chinese subjects [16].…”
Section: Discriminant Item Analysismentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies have generally found little or no influence of age, education, or gender on the ADAS-Cog score, although exceptions [2,15] to this general finding have also been reported. The present finding that performance on the Chinese ADAS-Cog was unrelated to education except at the low end (between 0 and 6 years) of the education spectrum is similar to the finding on the MMSE from a community study of 5,297 Chinese subjects [16].…”
Section: Discriminant Item Analysismentioning
confidence: 73%
“…(ii) Objects used for naming are replaced with colored photographs of objects that are more appropriate for our study population. (iii) The scoring of the naming item is simplified in the following manner: a failure is defined as an inability to correctly name an object or a finger within the time limit; the scores (and their corresponding numbers of failures) are 0 (0-2), 1 (3-5), 2 (6-8), 3 (9-11), 4 (12)(13)(14), and 5 (15)(16)(17). (iv) For the praxis item of using an envelope, the subject is asked to write the name only (without writing the address) and to point to the location of stamp placement (instead of actually putting on the stamp).…”
Section: Description Of the Chinese Adas-cogmentioning
confidence: 99%
“…Além disso, os grupos com maiores escolaridades apresentaram desempenhos superiores aos com menos escolaridade (Gráfico 1). Portanto,o escore total, que representa o comprometimento cognitivo apresentado ou a gravidade do quadro demencial, esteve para os analfabetos abaixo das notas de corte apresentadas na literatura 11,13,14,16,[26][27][28] , o que coincide com estudos realizados com outras escalas, como o MEEM 9 e a Adas-cog 29 dentre outras 30,31 .…”
Section: Discussionunclassified
“…A lower educational level is related to a worse performance in the tests in most of the studies with ADAS (11,25,(27)(28)(29). We observed that there is a significance in the education variable between and within groups.…”
Section: Discussionmentioning
confidence: 99%